الستارة الدخانية للغة : مجاز "الإعصار" في رواية الزمن الموحش (1973) لحيدر حيدر (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study attempts a critical investigation of the narrative strategies involved in structuring the narrative of Haydar Haydar’s Solitary Times (1973). It also aspires to examine how the major thematic elements—alienation, frustration, rage at repressive historical systems, and the “ laws of inertia”—are reproduced and enhanced in the narrative strategies on which the narrative structures itself. On the other hand, it tries to establish textual and thematic connections between the `spatial form` of the novel, and what is suggested as the `whirlwind` metaphor permeating its narrative moves. One major issue tackled in this essay is the use of a highly-poetic narrative language that functions as a smokescreen blurring characters and situations, rather than as a tool of unmasking and revealing their uniqueness and dynamism. تحاول هذه المقالة تقديم دراسة نقدية للاستراتيجيات السردية التي تبني عليها رواية الزمن الموحش (1973) لحيدر حيدر. كما أنها تطمح إلى البحث عن الطريقة التي تتم فيها إنتاج المواضيع الرئيسية – الغربة والإحباط والأنظمة التاريخية القمعية و"قوانين العطالة" –وتعزيزها من خلال هذه الاستراتيجيات السردية التي تؤسس البنية السردية نفسها عليها. ومن جهة أخرى, تحول هذه الدراسة تأسيس روابط موضوعاتية ونصية بين الشكل المكاني للرواية وما تقترح تسميته مجاز الإعصار الذي يتخلل حركاتها السردية . كما أن إحدى القضايا الرئيسة التي تعالجها هي استخدام لغة سردية شعرية تعمل بمثابة ستارة دخان تحجب الشخصيات والأوضاع السردية بدلاً من كونها أداة لإزالة الأقنعة وإلقاء الضوء على فرادة هذه الشخصيات والأوضاع وحيويتها.